Unlocking Inclusive Growth: The Impact of Shariah Investment in Indonesia - Indra, Indra; Ibrahim, Muhammad Yusuf (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2023)
This study investigates the role of Shariah investment in Indonesia's inclusive growth. Shariah investment is measured in terms of Shariah stocks and sukuk. As determinants of inclusive growth, the study also includes several control variables adopted from separate literature, including the effect of COVID-19. In contrast to previous research, testing is conducted using a variety of inclusive growth metrics. Using principal component analysis (PCA) to compute the composite index of inclusive growth and time series regression models with monthly data at the national level from 2011 to 2022, this study finds three main conclusions. Evidence shows that Shariah investment contributes to inclusive growth in Indonesia, but the effects vary. Shariah stocks significantly affect poverty and unemployment, whereas Sukuk affects poverty and inequality. Both contributed to improving the Human Development Index (HDI) and inclusive growth. This study also revealed that COVID-19 was instrumental in reducing Indonesia's inclusive growth performance. This study complements prior empirical research on inclusive growth issues in Indonesia by examining the role of Islamic economics and finance. This research contributes to future policy initiatives to strengthen Indonesia's inclusive growth.JEL Classification: D24, O14, O4How to Cite:Indra & Ibrahim, M. Y. (2023). Unlocking Inclusive Growth: The Impact of Shariah Investment in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 263-274. https://doi.org/10.15408/sjie.v12i2.31935